Surgical Management of Craniosynostosis—Between the Past and the Future: A Comprehensive Review of the Literature - Fouda, Mohammed A (Journal of Pediatric Neurology, 2023)
Cranial sutures are fibrous joints between the bones of the cranial vault, acting as centers of osteogenesis of the embryonic mesenchyme. Skull growth is a strictly regulated process, controlled by several genetic pathways. A minor perturbation of these pathways may lead to premature fusion of the cranial sutures. Craniosynostosis occurs as a result of the premature fusion of the cranial sutures. The incidence of craniosynostosis is approximately 1 in 2,500 live births. Syndromic craniosynostoses such as Apert, Crouzon, and Pfeiffer comprise 15% of patients, while nonsyndromic craniosynostosis represents 85% of all patients. By the late 1800s, Lannelongue (Paris, 1890) and Lane (San Francisco, 1892) attempted the first surgical intervention (strip craniectomy) for the management of craniosynostosis. The inadequacy of simple suturectomies and strip craniectomies in the management of craniosynostosis led to the innovation of more complex procedures such as frontoorbital advancement and posterior cranial vault distraction. However, these extensive surgical interventions are lengthy procedures and associated with more blood volume loss which requires blood transfusion. These limitations led to the modern era of minimally invasive endoscopic techniques. In this paper, we reviewed the body of the literature on the evolution of surgical management of craniosynostosis over the last century and the possible future directions.
Keywords: craniosynostosis; minimally invasive; endoscopic; fronto-orbital advancement; posterior cranial vault distraction; springs; helmet therapy